Kemampuan Guru PAI dalam Menggunakan Media Pembelajaran Berbasis IT pada SMP Negeri 11 Lhokseumawe - Dewi, Safrina (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2023)
The goal to be achieved in this study is to find out the efforts of Islamic Religious Education (PAI) teachers at SMP Negeri 11 Lhokseumawe in using Information and Technology (IT) based learning media. This study uses a qualitative approach. Data collection was carried out by observation, interviews, and documentation studies. The collected data is analyzed by reducing data, presenting data, and drawing conclusions or verification. The results found in this study indicate that in the use of IT-based learning media, teachers at MTSN 11 Lhokseumawe perform the following steps: 1) identifying suitable materials presented using IT-based teaching media, 2) training on developing learning media, 3) implementing the mentoring programs, 4) buying a laptop, 5) making a schedule for using the LCD Projector, and 6) including plans to use IT in the RPP. While the obstacles faced can be identified in several ways, including: 1) technological incompetence; the competence of PAI teachers is limited to the use of IT, 2) lack of availability of IT laboratory space, 3) inadequate availability of LCD projectors, and 4) limited internet network.